Drama as a community engagement strategy for malaria in rural Cambodia - Lim, R; Tripura, R; Peto, TJ; Sareth, M; Sanann, N; Davoeung, C; Nguon, C; Cheah, PY (Wellcome Trust, 2018)
Background Countries in Southeast Asia are working to eliminate multidrug-resistant falciparum malaria, a major cause of mortality in tropical regions. Malaria is declining but transmission persists in many rural areas and among forest workers and isolated populations. In these remote communities, conventional health services and education are limited. Mobilising and educating these populations require new approaches as many people are illiterate and do not attend village meetings. This article describes a qualitative study to assess the feasibility of a drama project as a community engagement strategy. Methods A drama project was conducted in twenty villages in Cambodia with three key messages: to use insecticide-treated bednets and repellents, to get early diagnosis and treatment, and to learn about risks of forest-acquired malaria. Qualitative interviews were conducted with the drama team members, village malaria workers, local health staffs and villagers, to explore the feasibility of using drama to engage the community and the associated challenges. Results 29 people were interviewed, which included 18 semi-structured interviews and one focus group discussion. Analysis of the interviews resulted in development of the following seven themes: i) exposure to malaria and engagement activities, ii) readiness and barriers to participation, iii) understanding and learning about malaria using drama, iv) entertainment value and engagement method preferences, v) challenges to community engagement, vi) future participation and vii) sustainability. The event saw a very positive response, with an encouraging average participation rate of 66%. The project faced several challenges including logistic problems, rescheduling due to raining season, and time- and budget-constraints. Conclusions Our evaluation demonstrated that the drama project was feasible in promoting awareness and understanding of malaria prevention and control. Audience members perceived drama as entertaining and as the preferred choice of engagement activity. Participatory drama could be considered as part of the community engagement for malaria elimination.